1979
DOI: 10.1007/bf02408082
|View full text |Cite
|
Sign up to set email alerts
|

A cat model for the evaluation of mechanisms of bone resorption: Induction of bone loss by simulated immune complexes and inhibition by indomethacin

Abstract: When simulated immune complexes (SIC) (heat-aggregated IgG) possessing many of the properties of true antigen-antibody complexes were injected via the root canal into the periapical tissues of cat maxillary cuspids, radiographically and histologically evident bone resorption occurred at these sites within 7 days. Bone loss was accompanied in all cases by inflammation of the surrounding collagenous connective tissues and was characterized by the presence of osteoclasts. Bone resorption, but not the accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…These findings provide clarification to an earlier report that indomethacin reduces the extent of bone resorption in endodontic lesions (23). Endodontic lesions have been associated with multiple proinflammatory cytokines and chemokines.…”
Section: Lesions Of Endodontic Originsupporting
confidence: 87%
“…These findings provide clarification to an earlier report that indomethacin reduces the extent of bone resorption in endodontic lesions (23). Endodontic lesions have been associated with multiple proinflammatory cytokines and chemokines.…”
Section: Lesions Of Endodontic Originsupporting
confidence: 87%
“…Stashenko et al (23) demonstrated that IL-1 receptor-antagonist may be used in animals to reduce bone-resorbing activity and the formation of periapical lesions. Similarly, NSAIDs were successfully used for a similar purpose in experimental and human periodontal diseases, as well as in the cat model for periapical lesion (44,45). These two approaches are directed at either blocking the binding of the already produced cytokine to its target cells or interfering with its action on osteoclasts and osteoblasts, which involves prostaglandin production (25,26).…”
Section: Future Perspectivementioning
confidence: 99%
“…It was found to be a significant inhibitor of bone resorption in both tissue cultures and animal studies. In an early report of indomethacin and its effects on bone loss, Torbinejad et al 139 administered indomethacin to cats that had been given an injection of simulated immune complexes. The induced bone loss in the periapical regions was inhibited by the administration of indomethacin.…”
Section: Periodontal Disease Progressionmentioning
confidence: 99%